Thermodynamic Performance and Wave Propagation Sensor System of Fiber Bragg Grating in Liquid Media - Romi F. Syahputra; Ridho Kurniawan; Yunita I. Lubis; Mesra Sania; Okfalisa Okfalisa; Saktioto Saktioto (Universitas Ahmad Dahlan, 2018)
Although the measurement of liquids temperature is commonly used by Fiber Bragg Grating (FBG) sensor but its thermodynamic performance has interesting phenomena. This paper proposes the measurement and simulation of liquids temperature using FBG. Laser diode was launched into human blood, water, and vegetable oil, then transmitted power is measured by optical powermeter to determine its corresponding temperature. The results showed that the increasing temperature changes led to the widening of the wave shift. The largest change of wavelength is water temperature and the smallest One is vegetable oil temperature. Increase in liquid temperature causes the output power is greater. FBG simulation of sine and square function are also designed for temperature range of 30°C to 41°C with matrix transfer method based on coupled mode theory. Peak value of transmission spectrum of each function is shown by the change of temperature which indicates the sensor is sensitive to sine and square function variations. The peak at temperature of 30°C for each sine and square are -78.32 dB and -102.66 dB and increased to 41°C at 46.72 dB and -79.89 dB, respectively.